Pengembangan Bahan Ajar Cerita Rakyat Tana Luwu Terintegrasi Pendidikan Karakter di Sekolah Dasar - Wahyuni, Dian; Nursyamsi, Nursyamsi; Firman, Firman (Socratika: Journal of Progressive Education and Social Inquiry, 2024)
This research aimed to develop an innovative Printed Teaching Material (Module) based on Tanah Luwu folktales that meets the needs of students in Sekolah Dasar Negeri (SDN) 657 Passampa Kab. Luwu Sulawesi Selatan. The findings indicate that the development of teaching materials grounded in folktales can enhance the quality of education and students' critical thinking skills. The validity and practicality of the developed teaching materials have been confirmed by experts, teachers, and students, with overwhelmingly positive feedback. The implications of this research emphasize the importance of integrating folktales into education as a strategy to preserve culture and increase the appeal of learning. The study also encourages the development and application of folktale-based teaching materials in school curricula, which can assist teachers in creating more interactive and meaningful learning experiences for students. Overall, this research provides a significant contribution to improving the quality of education in Indonesia by promoting a more contextual and innovative approach to learning.